Equations of state in three centuries. Are we closer to arriving to a single model for all applications?. (May 2020) - Kontogeorgis, Georgios M.; Liang, Xiaodong; Arya, Alay; Tsivintzelis, Ioannis
Highlights: Cubic and non-cubic equations of state are reviewed. Association models are important for advanced applications. Single thermodynamic model for all applications. Abstract: Equations of state represent the cornerstone of thermodynamic models. They have the potential of being used for a wide range of properties, systems and conditions and thus in many practical applications of relevance to chemical, petroleum, environmental and other types of engineering disciplines. Equations of state with great potential appeared first in the 19th century in the form of the van der Waals (and other similar ones) and for almost 150 years, both these classical and more advanced equations of state have shown great potential. This manuscript presents the opinion of the authors on the capabilities - limitations, current status and future challenges of equations of state. It is not a comprehensive review and only equations of state which, according to the authors' views, have potential general applicability are discussed. This work is an account of the authors' experience based on their many years' collaboration and involvement with a wide range of diverse general equations of state. We feel that, while the topic is still of great importance, it has stagnated a bit during the 21st century. We also believe that several of the personal views expressed in this manuscript may be contested and diverse opinions are available, but we consider that, should this be the case, this is also very positive as this manuscript can contribute to a healthy debate on the actual status and future perspectives of this important field.